Risk factors of stunting in toddler aged 24-59 month - Hutabarat, Melba Riska Utami; Irwanto, Irwanto; Sulistiawati, Sulistiawati (Jurnal Kebidanan, 2021)
Stunting is a chronic condition that describes growth retardation due to long-term malnutrition. Prevalenced of stunting in Cempaka subdistrict in 2017 reached 51.25% and the stunting incidence was widely found in toddler aged 24 – 59 month. The purpose of study was to analyze the risk factors of stunting in toddler age 24 - 59 month in Cempaka subdistrict, Banjarbaru. The research was an observational analytic with case control approached. The sample was 200 peoples included mothers and toddlers aged 24-59 months according to the inclusion criteria. Subject selection by cluster random sampling for selected the group’s sample and simple random sampling for selected its sample. The data was tested using Chi Square and logistic regression at significance level α = 0.05. This analysis was performed to find the association of stunting with selected factors. The resulted of the multivariate analysis showed short birth’s length had (p=0.00; OR 14.1) and the age 24-36 month had (p=0.01; OR 1.6) while mother’s height, sex, socioeconomic status, parent’s educational status, mother’s age married, mother's malnutrition status, birth weight, exclusive breastfeeding and complementary food’s time is not a factor in stunting. The conclusion of this study that short birth’s length and aged 24 – 36 month are the most dominant risk factor of stunting in toddler aged 24 – 59 month.